Avaliação do papel prognóstico do biomarcador vimentina no câncer de colo uterino - Santana, Flávia de Castro (2018)
Cervical cancer is a common disease in developing countries and in Brazil it is considered a serious public health problem, since diagnosis is still performed in late stages of the disease. An event called epithelial-mesenchymal transition (EMT) is important in tumor progression, since it interferes in the process of invasion and metastasis. EMT has been frequently studied in human cancers. Aberrant expression of several biomarkers is often observed in the EMT process, including the expression of Vimentin. The aim of this study was to evaluate the expression of Vimentin in cervical carcinomas investigating the prognostic role of this biomarker. Vimentin expression was evaluated by immunohistochemistry in 111 cases of cervical carcinomas and levels of expression were evaluated in relation to clinic pathological and prognostic aspects of the tumors. According to the results, aberrant expression of Vimentin was observed in 100% of the carcinomas. Vimentin overexpression (> 40%) was observed in 28 cases (25.2%), however, it was not associated with clinic pathological aspects and prognosis of cervical carcinomas. The overall survival for the group was 65.8% and it was influenced by age, the size of the tumor, the presence of lymph node metastasis, the presence of distant metastasis and by clinical staging. However, it was not influenced by Vimentin expression. Based on the results obtained in this study, the Vimentin expression was not considered a prognostic factor for cervical carcinomas.